Separate the variables:
![y' = (dy)/(dx) = (2x)/(1+2y) \implies (1+2y) \, dy = 2x \, dx](https://img.qammunity.org/2023/formulas/mathematics/college/cvf3kiqi74x8623oxvdqbnu99aaha1s2ha.png)
Integrate both sides:
![\displaystyle \int(1+2y) \, dy = \int 2x \, dx[/tex\</p><p>[tex]y + y^2 = x^2 + C](https://img.qammunity.org/2023/formulas/mathematics/college/zhjqrais67onuf426ux6lnxand59kj5nai.png)
Use the given initial condition to solve for C :
![1 + 1^2 = 1^2 + C \implies C = 1](https://img.qammunity.org/2023/formulas/mathematics/college/9fg6ekd5oerdpaj3qjafetm839o254hqg1.png)
So the particular solution is
![\boxed{y + y^2 = x^2 + 1}](https://img.qammunity.org/2023/formulas/mathematics/college/2g7n1w7hvbb05zy4gaedqkhr6f00y8h3yo.png)
which you can also solve explicitly for y as a function of x. By completing the square on the left side, we have
![y + y^2 = x^2 + 1](https://img.qammunity.org/2023/formulas/mathematics/college/g79ceomoe2ohj0ox1abvv8h758e9bdfcb0.png)
![\frac14 + y + y^2 = x^2 + \frac54](https://img.qammunity.org/2023/formulas/mathematics/college/y1nk4h97bu2mj7qyfewpqbagtgkyu36yzb.png)
![\left(\frac12 + y\right)^2 = x^2 + \frac54](https://img.qammunity.org/2023/formulas/mathematics/college/fbs03ocln4nxfnx8c5ff5xduhyljucoibx.png)
![\frac12 + y = \pm √(x^2+\frac54)](https://img.qammunity.org/2023/formulas/mathematics/college/r72xcm7om8flf95ynqz5lq1u1ikbbo3zmx.png)
Note that y(1) = 1 is positive, so the right side should involve the positive square root:
![\frac12 + y = √(x^2+\frac54)](https://img.qammunity.org/2023/formulas/mathematics/college/4v965n51c1a8chxy2u8qo6hvyuxqluev8v.png)
![\boxed{y = -\frac12 + √(x^2+\frac54) = -\frac12 + \frac12 √(4x^2+5)}](https://img.qammunity.org/2023/formulas/mathematics/college/4rlgqj92mo9megeg9torhh1taexlqu4pea.png)